Estudos em Pitcairnia azouryi (Bromeliaceae), uma espécie endêmica de inselbergues da Floresta Atlântica - Manhães, Vitor da Cunha (2015)
This study reports the discovery of new areas of occurrence of Pitcairnia azouryi Martinelli & Forzza, and the study of their populations regarding its genetic diversity, the amount of nuclear DNA and the chromosome number. Seven new areas of occurrence for this species were located between the northern state of Rio de Janeiro (RJ) and the southern state of Espírito Santo (ES), and georeferenced to the other studies. Leaf samples of 13-15 individuals were collected in five of these populations (PLB - Pedra Lisa Burarama, PA - Pedra das Andorinhas, PTI - Pedra Três Irmãs, PPC - Pedra Parada Cristal and PLC - Pedra Lisa Campos), totaling 66 individuals. Nine SSR markers were used in PCRs. Genetic polymorphisms were identified from polymorphism between individuals sampled, detected by electrophoresis on acrylamide gel 8%. The parameters of diversity and genetic structure of populations were calculated using the software Fstat, PopGene and Structure. The flow cytometry analysis was performed using leaf samples obtained from adult individuals of five populations. Cytogenetic analyzes were performed with roots obtained from germinated seeds collected in two populations. The nine SSR primers produced satisfactory amplification products, and proved to be polymorphic. The number of alleles per loci ranged between two and eight. The values of gene diversity index (Gd) and the fixation index (Fis) in populations ranged from 0.459 to 0.578 and 0.047 to 0.208, respectively. The Fst values observed showed that 81.20% of the total genetic variation is found within populations and the occurrence of gene flow (Nm) 1,073 (average number of migrants per generation). Bayesian analysis indicated that a model of k = 3 populations is able to better capture the variation in the data on the genetic structure. The high variation of fixation index added to the large genetic variation within and moderate genetic differentiation among populations suggest the occurrence of the founder effect in the dispersion of new individuals in new locations, followed by genetic drift, especially for the population of Campos dos Goytacazes. The flow cytometry analysis showed that the nuclear DNA content is 2C = 1.16 picograms in all populations analyzed, except on PLC population, in which was measured twice of DNA content (2C= 2.32 picograms). This result was explained by cytogenetic analysis which revealed individuals with 2n = 50 chromosomes in ES and individuals 2n = 100 chromosomes in RJ. This result may be due for PLC's geographical isolation, environmental characteristics of different evolutionary processes.